KEWIRAUSAHAAN BERBASIS SPIRITUAL HINDU DI BALI - Bontot, I Nyoman; I Wayan Widnyana (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
The high intensity of the yajÅˆa ceremony in Bali has the opportunity to impoverish the Hindu community in Bali. Because the implementation of the yajÅˆa ceremony is complex and takes a long time for the Hindu community to work for a living. In addition, the implementation of the yajÅˆa ceremony is quite costly. On the other hand, the implementation of the yajÅˆa ceremony in Bali also creates business opportunities for traders (entrepreneurs). However, the business opportunities that arise from the implementation of the yajÅˆa ceremony in Bali are actually exploited by more immigrants. This happens because his entrepreneurial spirit is still low, much influenced by agrarian culture, prestige, lack of talent to become traders, is bound by Pakraman village activities, and capital constraints. This study examines the meaning and meaning of entrepreneurship in life, the concept of entrepreneurship in Hinduism, and business opportunities in Hindu life in Bali.The concept of entrepreneurship in Hinduism is taught in the Holy Bible Atharvaveda III.24.5, Canakya Nitisastra I.9, and Canakya Nitisastra VI.5. In addition, the teachings to become entrepreneurs (entrepreneur) are also taught regularly through the Matiti Swara ritual at the Ngusaba Kedasa Ceremony at Ulun Danu Batur Temple, Batur Village, Bangli Regency.A promising business opportunity to be involved in the life of Hinduism in Bali is to fulfill the needs of the yajÅˆa ceremony, in addition to meeting the consumption of the general public. According to Geertz (2000: 164), periodic major ceremonies (redistributive) in Bali were used as one of the four trade flows in Bali by kings (puri-puri) in the 19th century. Thus, people from various professions can take advantage (profit) from the periodic implementation of these major ceremonies.